2013
DOI: 10.1016/j.electacta.2013.09.116
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the electrochemical behaviour of TiMo alloys in simulated physiological solutions

Abstract: This paper addresses on the electrochemical behaviour of three TiMo alloys exposed to simulated physiological environments. Their stability and corrosion resistance was characterized in order to explore the potential application for the manufacturing of implant materials. Ringer's solution together with an acidic modification of the Ringer's solution (pH = 3.1) at room temperature were considered. Both electrochemical methods (namely, potentiodynamic polarization curves and electrochemical impedance spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 54 publications
4
40
0
Order By: Relevance
“…Moreover, alloying titanium with Mo β-stabilizers improves the corrosion resistance [4][5][6][7][8][9][10], in addition to adequate mechanical compatibility and good cytocompatibility [11][12][13][14][15][16] despite one controversial report [17]. Unfortunately, titanium and molybdenum are difficult to alloy through a conventional melting-casting process due to the big difference in melting point and specific gravity between the two metals.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, alloying titanium with Mo β-stabilizers improves the corrosion resistance [4][5][6][7][8][9][10], in addition to adequate mechanical compatibility and good cytocompatibility [11][12][13][14][15][16] despite one controversial report [17]. Unfortunately, titanium and molybdenum are difficult to alloy through a conventional melting-casting process due to the big difference in melting point and specific gravity between the two metals.…”
Section: Introductionmentioning
confidence: 95%
“…The maps obtained by SECM provide information of the chemical activity of the oxide layer/electrolyte solution interface. Bolat et al [22] studied the electrochemical behaviour of three Ti-Mo alloys exposed to simulated physiological environments by SECM and observed that the oxide films formed on the surface of the alloys exhibit dielectric characteristics towards charge transfer.…”
Section: Introductionmentioning
confidence: 98%
“…The presence of organic topcoat shifted to OCP to nobler values at the end of the monitoring period. It is well-known from the literature that more cathodic values of the OCP indicate an electrode surface more stable and less susceptible to corrosion reactions [26]. In this respect, the presence of the organic layer improved the thermodynamic stability of the system.…”
Section: Corrosion Behaviormentioning
confidence: 97%